Constitutional imaginaries a theory of European societal constitutionalism - Přibáň, Jiří 1967- (Routledge, Taylor & Francis Group, 2022)
"Constitutional imaginaries invite constitutional and political theorists, philosophers and sociologists to rethink the concept of constitution as the normative legal limitation and control of political power. They show that political constitutions include societal forces impossible to contain by legal norms and political institutions. The constitution of society as one polity defined by the unity of topos-ethnos-nomos, that is the unity of territory, people and their laws, informed the rise of modern nations and nationalisms as much as constitutional democratic statehood and its liberal and republican regimes. However, the imaginary of polity as one nation living on a given territory under the constitutional rule of law is challenged by the process of European integration and its imaginaries informed by transnational legal and societal pluralism, administrative governance, economic performativity and democratically mobilised polity. This book discusses the sociology of imagined communities and the philosophy of modern social imaginaries in the context of transnational European constitutionalism and its recent theories, most notably the theory of societal constitutions. It offers a new approach to the legal constitutions as societal power formations evolving at national, European and global levels"
Keywords: Europäische Union; Rechtstheorie; Verfassungsrecht; Gesellschaft; Constitutional law / Social aspects / Europe